Naringin protects against diabetic cataracts in rats by modulating oxidative stress and inflammation - Meng, Gaoqiang; Meng, Li; Xu, Yalong (Archives of Biological Sciences, 2025)
Paper description: Naringin contributes to the development of effective interventions for diabetic cataracts. This study elucidates its therapeutic potential and underlying mechanisms. Diabetic rats treated with naringin had a significantly lower incidence and severity of cataracts than vehicle-treated counterparts. Naringin treatment effectively mitigated detrimental effects by enhancing Nrf2-mediated antioxidant defenses and suppressing NF-κB-driven inflammatory responses. These results enhance our understanding of the role of natural compounds in managing diabetic complications and lay the groundwork for future research and potential clinical applications. Abstract: This study investigated the efficacy of naringin, a bioflavonoid recognized for its antioxidative and anti-inflammatory properties, in preventing the development of diabetic cataracts. Streptozotocin (STZ)-induced diabetic rats and age-matched controls were treated either with naringin or a vehicle for 12 weeks. Cataract formation scores, oxidative stress markers, proinflammatory cytokines, and the transcription factor Nrf2 and NF-κB activities in the lens were assessed. Diabetic rats treated with naringin had a significantly reduced incidence and severity of cataracts compared to vehicle-treated counterparts. Vehicle-treated diabetic rats had elevated oxidative stress and inflammation in the lens, characterized by decreased Nrf2 activity and increased NF-κB activity. Naringin treatment effectively mitigated these detrimental effects by enhancing Nrf2-mediated antioxidant defenses and suppressing NF-κB-driven inflammatory responses. Importantly, naringin did not significantly alter blood glucose levels in diabetic rats, indicating its cataract-preventive effects were independent of glycemic control. Naringin has a protective role against the onset and progression of diabetic cataracts by modulating key oxidative and inflammatory pathways in the lens. These findings suggest it is a promising therapeutic agent for preventing diabetic cataracts.